2015
DOI: 10.1053/j.ajkd.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Death Among Elderly Dialysis Patients: Development and Validation of a Risk Score to Assist Shared Decision Making for Dialysis Initiation

Abstract: Background A shared decision-making tool could help elderly advanced chronic kidney disease (CKD) patients decide about initiating dialysis. Since mortality may be high in the first few months after initiating dialysis, incorporating early mortality predictors in such a tool would be important for an informed decision. Our objective is to derive and validate a predictive risk score for early mortality after initiating dialysis. Study Design Retrospective observational cohort, with development and validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(161 citation statements)
references
References 40 publications
(41 reference statements)
12
146
2
1
Order By: Relevance
“…In elderly patients, impaired mobility was associated with 1-year mortality in an univariate analysis of a single publication (OR, 4.22; 95% CI, 1.87 to 9.57) (18), and total dependence for transfers was independently associated with 3-and 6-month mortality (OR, 6.53; 95% CI, 5.38 to 7.92 and OR, 1.7; 95% CI, 1.4 to 2.0, respectively) (25,26). Dependence in ADLs was associated with mortality in two of three studies (OR, 1.41; 95% CI, 1.08 to 1.85) (31,42). Impaired cognitive function, defined as severe behavioral disorder, was associated with mortality as well (25,26), but two smaller studies did not find this relation (29,31).…”
Section: Relation Of Geriatric Impairments and Mortalitymentioning
confidence: 92%
See 1 more Smart Citation
“…In elderly patients, impaired mobility was associated with 1-year mortality in an univariate analysis of a single publication (OR, 4.22; 95% CI, 1.87 to 9.57) (18), and total dependence for transfers was independently associated with 3-and 6-month mortality (OR, 6.53; 95% CI, 5.38 to 7.92 and OR, 1.7; 95% CI, 1.4 to 2.0, respectively) (25,26). Dependence in ADLs was associated with mortality in two of three studies (OR, 1.41; 95% CI, 1.08 to 1.85) (31,42). Impaired cognitive function, defined as severe behavioral disorder, was associated with mortality as well (25,26), but two smaller studies did not find this relation (29,31).…”
Section: Relation Of Geriatric Impairments and Mortalitymentioning
confidence: 92%
“…The sample size ranged from 40 to 272,024 patients, and the mean age ranged from 53 to 82 years old. Seven studies focused exclusively on elderly patients (mean age ranging from 67 to 82 years old) (18,25,26,29,33,34,42), and one study performed a subgroup analysis of elderly patients (31).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Overall functional performance was assessed in 13 studies, with eight using the Karnofsky Performance Scale (KPS) (19)(20)(21)(22)(23)(24)(25)(26), one using the basic Activities of Daily Living scale (27), two using the World Health Organization performance scale (28,29), and two using a composite variable for assistance with daily living (30,31). Eight studies reported on the prevalence of functional impairment in patients reaching ESRD measured as impaired overall functional performance, which ranged from 21% to 85% (19,20,23,(25)(26)(27)29,30).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Eight studies reported on the prevalence of functional impairment in patients reaching ESRD measured as impaired overall functional performance, which ranged from 21% to 85% (19,20,23,(25)(26)(27)29,30). In all 13 studies, reduced functional performance was associated with a higher risk of adverse health outcomes, both after starting dialysis and CKM.…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…The focus for the European guidelines will be on identifying scores to distinguish between patients that may benefit from renal replacement therapy and those who may not [14,15]. How to integrate such scores in the decision to start dialysis (ranked 2 nd in our prioritization), and within a shared treatment decision-making process (ranked 10 th ) in general has been addressed by other guidelines [13,16].…”
Section: Discussionmentioning
confidence: 99%